2019
DOI: 10.1371/journal.pone.0224631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of F1 and F2 generations on genetic variability and working steps of doubled haploid production in maize

Abstract: For doubled haploid (DH) production in maize, F1 generation has been the most frequently used for haploid induction due to facility in the process. However, using F2 generation would be a good alternative to increase genetic variability owing to the additional recombination in meiosis. Our goals were to compare the effect of F1 and F2 generations on DH production in tropical germplasm, evaluating the R1-navajo expression in seeds, the working steps of the methodology, and the genetic variability of the DH line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Moreover, the discrepancy between HIR in 2012/2013 and 2014/2015 can be explained by natural selection disfavoring the haploidy-inducing gametes during selfing. From an evolutionary point of view, a higher proportion of haploids in the family caused by high HIR of the pollinator would result in reduced plant vigor, because haploid maize plants are less vigorous, often male sterile, and therefore generally less likely to produce progenies than diploid maize plants (Couto et al 2020), which explains the action of natural selection (Prigge et al 2012). The latter may also explain the difficulties of maintaining haploid inducers described by maize breeders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the discrepancy between HIR in 2012/2013 and 2014/2015 can be explained by natural selection disfavoring the haploidy-inducing gametes during selfing. From an evolutionary point of view, a higher proportion of haploids in the family caused by high HIR of the pollinator would result in reduced plant vigor, because haploid maize plants are less vigorous, often male sterile, and therefore generally less likely to produce progenies than diploid maize plants (Couto et al 2020), which explains the action of natural selection (Prigge et al 2012). The latter may also explain the difficulties of maintaining haploid inducers described by maize breeders.…”
Section: Resultsmentioning
confidence: 99%
“…Maize haploid inducer lines, when used as pollinators, trigger the production of seeds with a haploid embryo at a mean rate of 8% due to a hetero-fertilization together with failed egg-sperm cell fusion (Tian et al 2018). In spite of the successful development of maize haploid inducers in the tropics (Chaikam 2012, Couto et al 2020), compared to temperate conditions, data on this DH process are still scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were compared for HIR, diploid seed rate, and inhibition seed rate. Findings showed that HIR, inhibition seed rate, and diploid seed rate were 1.23, 23.48, and 75.21% for F 1 generation and 1.78, 15.82, and 82.38% for F 2 generation respectively (Couto et al., 2019). Conclusively stating that very high inhibition rate was observed in genetic background of tropical germplasm for expression of R1‐navajo phenotype.…”
Section: Phenotypic Markersmentioning
confidence: 99%
“…To obtain seeds from induction crosses marked by R1-nj, we used a haploid inducer population derived from a cross of two inducer lines (W23 and Stock6) with a maize hybrid adapted to tropical conditions. This inducer population has a dominant inheritance for the R1-nj marker and a putative haploid induction rate equal to 1.51% (Couto et al, 2019). As donors, we used two commercial singlecrosses, one from the flint and another from the dent heterotic group, where 50 unique plants from the haploid inducer were crossed with two plants from each donor.…”
Section: Plant Materials and Field Trialsmentioning
confidence: 99%